MP-15 Characterization of Infectious Bursal Disease Isolate with Propagation in Chicken Embryonated Eggs and Molecular Biology - . Syamsidar; Arini Nurhandayani; Steffi Ong; Aprilia Kusumastuti; Ardi Budi Prakoso; Gusti Ayu Yunanti Kencana (Hemera Zoa, 2018)
Infectious Bursal Disease (IBD), also known as Gumboro disease is one that has an adverse economic effect. This disease is a threat to the poultry industry (Mueller, 2003). Deaths in chickens caused by IBD can even reach 100%. Outbreaks remain widespread despite vaccination programmes (Soedoedono, 2001). In Indonesia, the IBD disease is the cause of high death rates in poultry from the very virulent IBD (vvIBD) throughout the year 2014. Prevention of the disease can be done through vaccination. However, a tight vaccination programme so not ensure the safety of poultry from IBD. Therefore, there is a need for a vaccine strain to be suitable with those in the field. This can be accomplished with collecting virus isolates from the field and identifying the suitable vaccine strain. The purpose of this research is to characterize virus IBD isolates through propagation in embryonated chicken eggs. In addition, molecular methods will be used from PCR to identification with sequencing.